Reading from this place? A personal reckoning with whiteness and Bible scholarship - Forster, Dion Angus (HTS teologiese studies, 2025)
This article offers a critical autoethnographic engagement with the enduring influence of whiteness in biblical scholarship. The author, a white South African New Testament scholar, reflects on how his theological formation and social location (which is marked by institutional privilege and Eurocentric frameworks), shaped his early interpretive practices and hindered more just, contextual readings of Scripture. Drawing on Welile Mazamisa’s challenge to ‘read from this place’, the article traces a personal and theological journey from detachment to engagement, from reader to hearer, from teacher to learner. Framed by decolonial hermeneutics and contextual theology, the author explores how encounters in the church, academy and society at large disrupted inherited paradigms and called forth new modes of interpretation rooted in solidarity and accountability. Some primary (South) African perspectives are engaged to illuminate the epistemic and ethical imperatives of reading from below. The article demonstrates how critical reflexivity and intercultural reading practices can help dismantle the hermeneutical injustices perpetuated by whiteness and recover liberative meanings obscured by dominant theological traditions.Contribution: This article contributes to ongoing conversations about decolonising biblical scholarship by providing a personal, methodologically rigorous case study. It models how critical autoethnography can serve as a theological practice of unlearning and reimagining, offering a path for scholars situated in privilege to read the Bible differently. By centring Southern African voices and interpretive traditions, the article advances the work of contextual, justice-oriented hermeneutics within and beyond the South African academy.